Proceso de atención de enfermería aplicado a la salud escolar de niños/as del 2do año de educación básica paralelo B de la Escuela Fiscal Mixta Julio María Montovelle - Valdiviezo Guajala, Magali Mireya (2014)
This research work is a descriptive cross-sectional study in a group of children from the Joint Fiscal school Julio María Matovelle in which was proposed as main objective : to apply the process of nursing care, based on the assessment of functional patterns Marjory Gordon in Children / sophomore as basic education , parallel " b" of the Fiscal school school Mary Matovelle July , and on this basis a proposed intervention to children / parents as and was developed by the school. The universe was composed 498 children / as, and the sample consisted of 32 children / as . To meet the objectives. An instrument to 36 children / school as, studying in the Joint Fiscal school "Julio María Matovelle " neighborhood Band on Avenida December 8 , which belongs to the area of inflow area of Health No. 3 was applied. whereupon it came to determine that from the instruments used , the patterns are affected : health perception , nutritional metabolic , cognitive / perceptual role / relationships. In children surveyed mostly there is the presence of dental caries, they self medicate , also claims to suffer domestic abuse , there is also trouble concentrating and understanding , which can affect school performance. After being analyzed the results obtained are represented in simple tables expressed in frequency and percentage and were able to establish the conclusions and recommendations respectively. The results are a basic and helpful for the preparation of the final report item so we can run the proposed intervention to provide information related to the preservation of health and recommendations that promote the health of children studying in the school Attorney Julio María Matovelle mixed city of Loja. Keyword: Nursing care process, school.